Public Diplomacy Communication by Indonesian Embassy Staff in Amsterdam to the Muslim Community: A Qualitative Study of Interaction and Perception - Sabena, Sabena (Baca Dulu Publisher, 2025)
This study aims to explore the public diplomacy communication practices carried out by Indonesian Embassy staff in Amsterdam with Muslim communities in Europe, focusing on interactions, perceptions, and engagement-building strategies. The research approach is qualitative, with a constructivist paradigm, emphasizing how actors construct meaning through social interactions, identities, and cultural contexts. Data were collected through in-depth interviews with Indonesian Embassy staff and members of Muslim communities in the Netherlands and several other European countries throughout 2024, and validated through data triangulation. Furthermore, recent academic literature on public diplomacy, the diaspora, and Muslim identity in Europe was used to strengthen the analysis. The results of the study indicate that Indonesian Embassy staff employed adaptive communication strategies involving face-to-face dialogue, cultural activities, and social media, thereby building trust, legitimacy, and a sense of belonging among the diaspora community. The Muslim community interpreted public diplomacy practices as a form of identity recognition, support for their aspirations, and a cultural bridge between Indonesia and Europe. This study confirms that public diplomacy is a co-constructive process, in which Indonesian Embassy staff and the community jointly construct meaning, social relations, and a shared identity. In conclusion, Indonesian Embassy staff in Amsterdam acted as strategic cultural mediators and were able to adapt communication to the socio-religious context. Participatory communication strategies proved effective in increasing community engagement, strengthening identity, and strengthening the legitimacy of the Indonesian Embassy in the eyes of the diaspora. The findings of this study provide practical contributions to public diplomacy policy, as well as theoretical contributions to the study of public diplomacy, diaspora, and Muslim transnational identity.